Imagem & tecnologia: webmuseu de arte - Lima, Fábio Rogério Batista [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
With the presence of Cyberspace, web museums emerged, which are characterized as informational environments with exhibitions of artworks presented virtually, affecting the use of the image. Using an access device to the Internet, anyone can visit the works of established artists without leaving the place they are, which is a characteristic of ubiquity (being present in several places at the same time) offered by information and communication technologies (ICT), which was possible only with the geographic displacement to in-person visits. The formal and the artworks contents transformation in its transposition into digital environments is a consequence of the passage of a semiotic structure to another, which causes changes in the aesthetic quality of the work produced in different support from the one which is being presented in the digital environment for the construction of imagery information (size, color, shape, etc.) in digital museums. The digitalization and transposition of artworks to digital catalogs (digital version of the traditional catalogs) and /or web museums, create simulacra of the original works and its organic and material form transforms into computer language of bits and bites. In this context, were analyzed the impacts that information and communication technologies (ICT) cause the aesthetics of images available in these environments. Using the bibliographic descriptive method, the objective was to determine the characteristics of printed artworks catalogs, museums and web museums websites to demonstrate their ... (Complete abstract click electronic access below)

Com o Ciberespaço surgiram os webmuseus, que se caracterizam como ambientes informacionais com exposições de obras de arte apresentadas virtualmente, afetando o uso da imagem. A partir de um dispositivo de acesso à rede Internet, qualquer pessoa pode visitar obras de artistas consagrados sem sair do lugar em que está, uma característica da ubiquidade (estar presente em vários lugares ao mesmo tempo) oferecida pelas tecnologias de informação e comunicação (TIC), o que era possível apenas com o deslocamento geográfico para visitas presenciais. A transformação formal e dos conteúdos das obras de arte na sua transposição para ambientes digitais é uma consequência da passagem de uma estrutura semiótica para outra, o que ocasiona mudanças na qualidade estética da obra produzida em suporte diferente daquele que está sendo apresentado no ambiente digital para a construção de informação imagética (tamanho, cor, forma, etc.) nos museus digitais. A digitalização e a transposição das obras de arte para catálogos digitais (versão digital dos catálogos tradicionais) e/ou nos webmuseus criam simulacros das obras originais e sua forma material e orgânica transforma-se em linguagem computacional de bits e bites. Nesse contexto, apresenta-se como proposta identificar as características que indicam as transformações da estrutura de apresentação da obra de arte na sua transposição para ambientes virtuais quando digitalizadas, uma vez que, a mudança de um sistema semiótico para outro ocasiona rupturas e mutações na qualidade estética da obra de arte produzida sobre um suporte e transferida para outro. Com uso do método bibliográfico descritivo, o objetivo foi verificar as características dos catálogos impressos de obras de arte, dos sites de museus e de webmuseus demonstrando suas semelhanças...
Keywords: Museus digitais; Arte - Catálogos; Tecnologia da informação; Semiotica e artes; Imagens, ilustrações, etc; Virtual museums